When to stop propranolol for infantile hemangioma - Chang, Lei (Sci Rep, 2017)
There is no definitive conclusion regarding the optimal timing for terminating propranolol treatment for infantile hemangioma (IH). A total of 149 patients who underwent detailed color Doppler ultrasound examination were included in this study. The characteristics and propranolol treatment of all patients were summarized and analyzed. Patients were divided into two groups according to the lesion regression rate. Among the 149 patients, 38 were assigned to the complete regression group, and 111 were assigned to the partial regression group. The age at which propranolol treatment started, duration of follow-up after treatment discontinuation and rate of adverse events were not significantly different between the two groups. The duration of oral propranolol treatment was shorter in the complete regression group. The age at which propranolol was terminated was younger in the complete regression group, and this group had a lower recurrence rate. Propranolol is safe and effective for the treatment of IHs that require intervention, but it should be stopped at an appropriate time, which is determined primarily by the lesion regression rate after propranolol treatment. Ultrasound is helpful in determining when to stop propranolol for IH.